2021
DOI: 10.2196/27047
|View full text |Cite
|
Sign up to set email alerts
|

Smart Home Sensing and Monitoring in Households With Dementia: User-Centered Design Approach

Abstract: Background As life expectancy grows, so do the challenges of caring for an aging population. Older adults, including people with dementia, want to live independently and feel in control of their lives for as long as possible. Assistive technologies powered by artificial intelligence and internet of things devices are being proposed to provide living environments that support the users’ safety, psychological, and medical needs through remote monitoring and interventions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…All studies were longitudinal, study duration was in the range of 1-3.5 years, with a mean of 2.3 years. This was the least represented of the three most common PPA variants, which might be expected since it is the most recently described 49 . Decline in IADLs was more significant that decline in BADLs, with marked decline in planning and execution 12 months after baseline 32 .…”
Section: Results For Specific Diagnostic Variants Bvftdmentioning
confidence: 78%
“…All studies were longitudinal, study duration was in the range of 1-3.5 years, with a mean of 2.3 years. This was the least represented of the three most common PPA variants, which might be expected since it is the most recently described 49 . Decline in IADLs was more significant that decline in BADLs, with marked decline in planning and execution 12 months after baseline 32 .…”
Section: Results For Specific Diagnostic Variants Bvftdmentioning
confidence: 78%
“…We found that a user-centric design involving older adults is essential for the successful adoption of technology [ 38 , 39 ]. System designers should strive to understand the requirements of older adults, incorporate their feedback, and adapt technology to meet age-related needs, such as changes in abilities, health status, living arrangements, and family structures [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…User-centred design techniques can help to prioritise system design according to the features most important to users. 35 Machine learning systems do not make absolute predictions, but evaluate outcomes according to probabilities. A machine learning model will only be accepted when it reaches a level of accuracy deemed acceptable: this is often done by splitting the available training data into sets, one used for training and one used to assess performance.…”
Section: Human-centred Designmentioning
confidence: 99%
“…User-centred design techniques can help to prioritise system design according to the features most important to users. 35 …”
Section: Introductionmentioning
confidence: 99%